Effect of Valeriana officinalis hydroalcoholic extract on Giardia lamblia cysts - Mohamadi Mona; Khalili Bahman; Taghipur Simin; Drees Fatemeh (Shahrekord University of Medical Sciences, 2015)
ntroduction: Giardia lamblia is an important and prevalent parasitic cause of diarrhea andgastroenteritis. Regarding the significance of giardiasis treatment particularly by medicinal plantsand G. lamblia resistance to chemical drugs, this study was conducted to study in vitro effect ofValeriana officinalis hydroalcoholic extract on G. lamblia cysts.Methods: In this experimental, laboratory study the hydroalcoholic extract of V. officinalis atconcentrations of 12.5, 25, 50, 100, and 200 mg/mL was applied on G. lamblia cysts. The findingswere compared with controls.Results: Mean results of the effect of V. officinalis hydroalcoholic extract at different concentrationson G. lamblia cysts after 1, 6 and 24 hours demonstrated that the extract at all concentrations causeda notable decrease in alive cysts, with more intensive effect at 100 and 200 mg/mL concentrationsand 100% fatality after 1 hour. As the extract concentration decreased, the speed of G. lamblia cystsinhibition declined.Conclusion: V. officinalis hydroalcoholic extract might be recommended as an effective compoundfor removing G. lamblia protozoan cysts, although further studies are needed to show this effect onhuman.